Redescription of Trichomycterus striatus (Meek & Hildebrand, 1913) (Siluriformes: Trichomycteridae), with notes on its geographic distribution - Angulo, Arturo; Donascimiento, Carlos; Lasso-Alcalá, Oscar M.; Farah-Pérez, Aldo; Langeani, Francisco; Mcmahan, Caleb D. (Zootaxa, 2018)
Trichomycterus striatus is herein redescribed, based on examination of the types and recently collected specimens, and its geographic distribution is updated. This species can be diagnosed from all other northeastern South American congeners by its variable coloration pattern consisting of a yellowish to light brown background with a black lateral band and/or small dark brown spots on sides or uniformly light brown and by the following combination of characters: teeth conical arranged in three to four irregular rows in both jaws; anterior section of infraorbital canal (sensory pores i1 and i3) present; sensory pores s6 paired, 11–23 opercular odontodes; 27–44 interopercular odontodes; seven to eight pectoral-fin branched rays; 36–37 free vertebrae; 12–14 ribs; cleithrum pierced by several foramina; and caudal fin truncate to rounded. Trichomycterus striatus occurs from southern Costa Rica [from the Pirrís (herein reported for the first time), Térraba and Coto River basins] to eastern Panama (in most of the main river basins in both the Pacific and Atlantic versants), being the sole representative of the family in lower Central American waters.